Applications of Induced Pluripotent Stem Cells in the Modeling of Human Inflammatory Bowel Diseases - Liu, Jingquan; Shi, Bin; Shi, Kai; Zhang, Hongze (Current Stem Cell Research & Therapy, 2015)
Inflammatory bowel diseases (IBDs) are chronic and involve the gastrointestinal tract; the two primary IBDs are ulcerative colitis and Crohn’s disease. Existing treatments for IBD include control of active inflammation and regulation of immune disorders, and commonly used drugs include salicylates, corticosteroids, and immunosuppressants. At the same time, an in-depth study of IBD pathogenesis promoted the acceptance of bioimmunotherapy by increasing numbers of people. However, long-term use of these drugs can cause adverse reactions that are difficult for patients to overcome, with limited efficacy for critically ill patients. Recent studies have found that stem cell transplantation is a new and effective therapy and IBD treatment, particularly for refractory cases. Stem cells, especially induced pluripotent stem cells (iPSCs), can differentiate into functional intestinal epithelia and their use avoids ethical issues arising from embryonic stem cells, providing a new kind of seed cell for alternative treatments for IBD. This paper reviews iPSCs as a potential new treatment for IBDs in order to provide an experimental and clinical reference.
Keywords: reprogramming